Kepuasan Pernikahan Ditinjau dari Berpacaran dan Tidak Berpacaran - Iis Ardhianita; Budi Andayani (Jurnal Psikologi, 2005)
Getting married  is perceived as an  important phase in human life‐cycle. Just like  fashion, marriage has also its own trend or mode. In Indonesia  the  legend  of   Siti   Nurbaya illustrating a kind of marital arrangement in, at least, the first half of the past century. Such a trend  in marriage is any more popular these days. Young people today mostly prefer to marry their own choices, those already bond in engagement or girl or boy  friends they already mate. Another kind  of  trend  has  appeared  recently.  Some moslems prefer to marry without the phase of dating or engagement. Some even marry ones chose, or arranged by their ustadz (spiritual leader). The purpose of this study is to find out whether  a  difference  in  the  premarital relationship(with versus without engagement or dating) affect couples’ marital satisfaction. The  result  shows  that  there  is  a  very significant difference in marital satisfaction between  dating  and  non‐dating  couples. Explanation upon the phenomenon discussed. Keywords: marital satisfaction, dating and non dating couples